Racial Differences in Atrial Cardiopathy Phenotypes in Patients With Ischemic Stroke. (23rd February 2021) - Kamel, Hooman; Alwell, Kathleen; Kissela, Brett M.; Sucharew, Heidi J.; Woo, Daniel; Flaherty, Matthew; Ferioli, Simona; Demel, Stacie L.; Moomaw, Charles J.; Walsh, Kyle; Mackey, Jason; De Los Rios La Rosa, Felipe; et al.
Abstract : Objective: To test the hypothesis that thrombogenic atrial cardiopathy may be relevant to stroke-related racial disparities, we compared atrial cardiopathy phenotypes between Black vs White patients with ischemic stroke. Methods: We assessed markers of atrial cardiopathy in the Greater Cincinnati/Northern Kentucky Stroke Study, a study of stroke incidence in a population of 1.3 million. We obtained ECGs and reports of echocardiograms performed during evaluation of stroke during the 2010/2015 study periods. Patients with atrial fibrillation (AF) or flutter (AFL) were excluded. Investigators blinded to patients' characteristics measured P-wave terminal force in ECG lead V1 (PTFV1 ), a marker of left atrial fibrosis and impaired interatrial conduction, and abstracted left atrial diameter from echocardiogram reports. Linear regression was used to examine the association between race and atrial cardiopathy markers after adjustment for demographics, body mass index, and vascular comorbidities. Results: Among 3, 426 ischemic stroke cases in Black or White patients without AF/AFL, 2, 391 had a left atrial diameter measurement (mean, 3.65 ± 0.70 cm). Black race was associated with smaller left atrial diameter in unadjusted (β coefficient, −0.11; 95% confidence interval [CI], −0.17 to −0.05) and adjusted (β, −0.15; 95% CI, −0.21 to −0.09) models. PTFV1 measurements were available in 3, 209 patients (mean, 3, 434 ± 2, 525 μV*ms). Black race was associated with greater PTFV1 in unadjusted (β, 1.59; 95% CI, 1.21–1.97) and adjusted (β, 1.45; 95% CI, 1.00–1.80) models. Conclusions: We found systematic Black–White racial differences in left atrial structure and pathophysiology in a population-based sample of patients with ischemic stroke. Classification of Evidence: This study provides Class II evidence that atrial cardiopathy phenotypes differ in Black people with acute stroke compared to White people.